Re-Emergence of Tetanus in a District Referral Hospital - HH, Ariff; A, Verghese; CMK, Brian (IIUM Medical Journal Malaysia, 2017)
Tetanus is an acute, potentially fatal disease caused by Clostridium tetani. It is characterized by generalized, painful spasms and rigidity of skeletal muscles. We present two fatal cases and discuss the potential causes that lead to mortality in cases of tetanus infection.